Neural Stimulation Hardware for the Selective Intrafascicular Modulation of the Vagus Nerve - I. Strauss; F. Agnesi; C. Zinno; A. Giannotti; A. Dushpanova; V. Casieri; D. Terlizzi; F. Bernini; K. Gabisonia; Y. Wu; D. Jiang; V. Paggi; et al. (IEEE, 2023)
The neural stimulation of the vagus nerve is able to modulate various functions of the parasympathetic response in different organs. The stimulation of the vagus nerve is a promising approach to treating inflammatory diseases, obesity, diabetes, heart failure, and hypertension. The complexity of the vagus nerve requires highly selective stimulation, allowing the modulation of target-specific organs without side effects. Here, we address this issue by adapting a neural stimulator and developing an intraneural electrode for the particular modulation of the vagus nerve. The neurostimulator parameters such as amplitude, pulse width, and pulse shape were modulated. Single-, and multi-channel stimulation was performed at different amplitudes. For the first time, a polyimide thin-film neural electrode was designed for the specific stimulation of the vagus nerve. In vivo experiments were performed in the adult minipig to validate to elicit electrically evoked action potentials and to modulate physiological functions, validating the spatial selectivity of intraneural stimulation. Electrochemical tests of the electrode and the neurostimulator showed that the stimulation hardware was working correctly. Stimulating the porcine vagus nerve resulted in spatially selective modulation of the vagus nerve. ECAP belonging to alpha and beta fibers could be distinguished during single- and multi-channel stimulation. We have shown that the here presented system is able to activate the vagus nerve and can therefore modulate the heart rate, diastolic pressure, and systolic pressure. The here presented system may be used to restore the cardiac loop after denervation by implementing biomimetic stimulation patterns. Presented methods may be used to develop intraneural electrodes adapted for various applications.